ANALISIS PENGARUH JUMLAH PENDUDUK, TABUNGAN, DAN INVESTASI TERHADAP TINGKAT PENDAPATAN PER KAPITA INDONESIA - Masniadi, Rudi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2012)
This research intent to know factor picture that regard to increase income / PDB per capita at Indonesia. In theoretical study, factor that regard perkapita's income for example population, savings and investment, as one is described in Model growth Theory Solow Swan. analisis's tool that is utilized is with Analisis's approaching bifilar Regression via methodics Ordinary Least Square (OLS). Of theory study and research result can be concluded that up to period 1990 2008 available negative correlation among propertied per capita with islandic growth, or gets to be said by resident growth cause decrease to income per capita Indonesia resident. In the meantime, savingses level variable (GDS) and investment (GDCF), even in little percentage give positiv's influence to income per capita resident.